Exploiting the Unique Properties of Lanthanide Complexes as FRET Probes: from Quantitation to Protein Dynamics. Issue 1 (1st September 2022) - Wheeler, Simon; Butler, Stephen J.
Abstract: Lanthanide complexes have a range of photophysical properties – large pseudo‐Stokes shifts, narrow linewidths, long emission lifetimes – that make them ideal as emissive probes. These same properties also render them excellent donors in assays relying on Förster resonance energy transfer (FRET). Over the last 20 years these assays have increased in sophistication so that a range of biological applications has now been demonstrated. These range from easy‐to‐use quantitation of proteins (a practical alternative to western blotting) to sophisticated experiments which give real‐time information on the movement of proteins or allow simultaneous readout of both agonist and co‐activator binding to a protein. We introduce the principles and difficulties of using such assays before surveying the full scope of what they can achieve and attempting to anticipate future developments in this area. Abstract : Lanthanide complexes are ideal donors for FRET (Förster resonance energy transfer) assays with a variety of applications from easy‐to‐use quantitation of proteins to sophisticated experiments giving real‐time information on the movement of proteins. This Review article introduces the principles of using such assays before surveying the full scope of what can be achieved and attempting to anticipate future developments in this area.